2016
DOI: 10.5958/0974-9357.2016.00044.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Nurses Role Overload, Burnout and Managerial Coping Strategies at Intensive Care Units

Abstract: Work life takes up an important place in human life, and an employee faces many stimuli from internal and external environments and is affected by them in a positive or negative way. Aim: was to investigate relationship among nurses role overload , burnout and managerial coping strategies at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…This positive relationship between job stress and burnout has an overall damaging effect on both the mental and physical aspects of the employees. This study has also reported a positive and significant relationship between role overload and occupational burnout which confirms the studies of Kilroy et al (2016), Mohamed (2016) and Vullinghs et al (2018). Again, by accepting role overload, the employees undergo so much stress which ultimately results in occupational burnout.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This positive relationship between job stress and burnout has an overall damaging effect on both the mental and physical aspects of the employees. This study has also reported a positive and significant relationship between role overload and occupational burnout which confirms the studies of Kilroy et al (2016), Mohamed (2016) and Vullinghs et al (2018). Again, by accepting role overload, the employees undergo so much stress which ultimately results in occupational burnout.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, various studies have also related the positive link between role overload and occupational burnout (Shupe, Wambaugh and Bramble, 2015;Kilroy et al, 2016;Mohamed, 2016;Vullinghs et al, 2018). Maslach (1982) defined burnout as an occurrence of a stressful working environment that eventually drained the employees psychologically.…”
Section: Role Overload Job Stress and Occupational Burnoutmentioning
confidence: 99%
“…Specifically, in addition to their traditionally normative caregiver role, physicians today are required to enact the roles of administrative bureaucrat, regulator, and salesperson. Indeed, HIT directs physician's attention to these diverse roles, increasing role demands and a concomitating role overload that has been associated with burnout [e.g., 77,78,79].…”
Section: Proposition 2b: Technology Demands That Workers Enact Competing Roles (P2b)mentioning
confidence: 99%
“…Dalam melakukan pelayanan kesehatan perawat memiliki peran yang penting karena berada dalam kontak langsung dengan pasien sehari-hari sehingga dituntut untuk selalu dapat menampilkan emosi positif di depan pasien sebagai citra perusahaan. Perawat dianggap sebagai profesi dengan pekerjaan yang penuh dengan tekanan karena mereka merawat sekelompok orang yang penuh tekanan yaitu pasien atau orang memiliki gangguan kesehatan (Mohamed, 2016).…”
Section: Pendahuluanunclassified